Migration intentions among nursing students in the Age of COVID-19: A mixed method scoping review - Ghimire, Animesh; Thapa, Basanta; Kumari Ranabhat, Mina (Journal of Chitwan Medical College, 2024)
Background: The global nursing shortage poses an immense threat to healthcare systems, worsened by the impact of the COVID-19 pandemic on an already challenged workforce. Understanding student nurses' migration intentions, influenced by the "medical brain drain" phenomenon, is crucial for developing strategies to mitigate this shortage. This scoping review synthesizes the factors influencing undergraduate nursing students' intentions to migrate, specifically examining the unique impact of the COVID-19 pandemic on these decisions. Method: Adhering to the Arksey and O'Malley framework and the PRISMA-ScR checklist, we conducted a comprehensive search across five databases (CINAHL, PubMed, Ovid MEDLINE, PsycINFO, Embase), focusing on primary research addressing undergraduate nursing student migration intentions between December 2019 and April 2024. Data from selected studies were systematically extracted and analyzed. Result: Key drivers of migration intent included economic aspirations, the pursuit of professional fulfilment, cultural and familial ties, anticipated quality of life changes, and the influence of educational and policy environments. The COVID-19 pandemic has magnified existing healthcare disparities, reshaping migration motivations and underscoring the need for adaptive educational and policy responses. Conclusion: Nursing student migration decisions are complex and driven by personal, socioeconomic, and global factors significantly influenced by the pandemic. Targeted policy and educational reforms are essential to enhance local opportunities and mitigate the nursing brain drain. By addressing these factors early, we can foster a committed, resilient nursing workforce capable of meeting future global healthcare challenges, ensuring a more robust and equitable healthcare system worldwide.